Brexit: a consequence of the European social and democratic deficit - Mavrozacharakis, Emmanouil; Tzagkarakis, Stylianos Ioannis; Kamekis, Apostolos (2017)
Abstract: The outcome of the recent referendum in the UK was straightforwardly affected by the policies followed by the EU. The main factors in which eurosceptics-populists had used in order to collect votes were both the immigration crisis (and the consequent EU policies) and the European political reactions to the economic crisis which increases EU powers, under the German supervision, and decreases national sovereignty. Although these two factors may seem different, they are directly linked as long as they comprise an outcome of the social and democratic deficit of the EU which increased concerns about the future effects in the UK and offered the opportunity for the cultivation of populist ideas. This article aims at indicating the main parameters of the European social and democratic deficit which affected Britons’ decision in the referendum while drawing the attention on the restructure of the European policy directions